PENGARUH NON DEBT TAX SHIELD, CORPORATE TAX RATE, TANGIBILITY DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN UTANG - maryanti; Benarda (Publika Citra Media, 2026)
All companies need to manage and optimize their debt policies to ensure effective financial and operational activities. This study aims to analyze and test the effect of non-debt tax shields, corporate tax rates, tangibility, and company growth on debt policy. The population in this study was 70 infrastructure sector companies listed on the Indonesia Stock Exchange. Fifteen companies were selected through a purposive sampling method. This quantitative research used the e-views 12 program and multiple regression analysis. The test results indicate that non-debt tax shields, corporate tax rates, tangibility, and company growth simultaneously influence debt policy. Partially, non-debt tax shields and corporate tax rates do not influence debt policy, while tangibility and company growth influence debt policy.